Kepemilikan Institusional sebagai Moderasi: Manajemen Laba, Financial Distress, Sales Growth terhadap Praktik Tax Avoidance - Moh Abdurrosyid; Mita Amalia Damayanti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This study aims to examine the effect of earnings management, financial distress and sales growth on tax avoidance practices with institutional ownership as a moderator. The population in this study are companies in the various industrial sectors listed on the Indonesia Stock Exchange for the 2016-2021 period. Through purposive sampling technique obtained a sample of 228 research data. The analytical method used is panel data regression and moderated regression analysis which is processed using Eviews 9. The results of this study indicate that earnings management has a significant positive effect on tax avoidance practices, financial distress has a significant negative effect on tax avoidance practices, sales growth has a significant negative effect on tax avoidance practices. tax avoidance, institutional ownership can weaken the effect of earnings management on tax avoidance practices, institutional ownership can weaken the effect of financial distress on tax avoidance practices, institutional ownership can strengthen the effect of sales growth on tax avoidance practices.